2014
DOI: 10.1007/s00423-014-1260-0
|View full text |Cite
|
Sign up to set email alerts
|

Complications after laparotomy for trauma: a retrospective analysis in a level I trauma centre

Abstract: Laparotomy for trauma has a high complication rate resulting in significant morbidity and mortality. Most events occur in the early postoperative period. Further prospective research needs to be conducted in order to identify possibilities to improve care in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 40 publications
3
21
1
Order By: Relevance
“…In addition, the use of larger volumes of intraoperative peritoneal irrigation render no additional benefit for the prevention of intraabdominal sepsis, wound complications (including wound infections and evisceration episodes), or anastomotic dehiscence and enterocutaneous fistula formation events. This is also in line with the most current literature on the subject [41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the use of larger volumes of intraoperative peritoneal irrigation render no additional benefit for the prevention of intraabdominal sepsis, wound complications (including wound infections and evisceration episodes), or anastomotic dehiscence and enterocutaneous fistula formation events. This is also in line with the most current literature on the subject [41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 91%
“…While there is experimental evidence of at least one benefit to the use of irrigation in trauma victims [39], our results strongly suggest an upper limit of 5L for the effluent. This has relevance for today's practice, since epidemiological evidence exist for the current use of Intraoperative Peritoneal Lavage for this indication in surgical practice [41][42][43][44][45][46][47][48][49][50]. Our trial has several limitations: Since damage control techniques were utilized when indicated (as per the contemporary accepted standard of care) it is very possible that the potential benefits and/or harms (or lack thereof) that the intervention has in this population remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, it is suggested that the exposure of most European surgeons to an emergency laparotomy in severely injured patients is declining [1]. Penetrating injuries are a frequent indication for laparotomy in trauma patients [2,3]. However, in most European countries, penetrating injuries are a rare phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have reported Clavien-Dindo complication scores following trauma 1012 but without an explanation regarding how any modifications were made or whether there were any issues with translating the scoring system from elective surgery to emergency trauma management. Furthermore, they do not cite any source or justification for their utilization of Clavien-Dindo.…”
Section: Discussionmentioning
confidence: 99%